Comparison of 2016 Bow, AHSP And Contractor Cost Budget Plans in Road Improvement Projects Gurindam Batam Center - Suriyanti Suriyanti; Ade Jaya Saputra (Fakultas Teknik Sipil dan Perencanaan, 2023)
The Cost Budget Plan (RAB) is prepared at the initial planning stage of a project. At planning stage, make a RAB intend to find out how much the cost required for building / developing the project. During preparation, it is very crucial to have budget approaching expense carried out on site therefore to avoid loss and achieve success in project. In Indonesia, there are few arrangements, namely the BOW method, the 2016 AHSP method, and the contractor method. The author calculates the Budget Plan using the BOW method, AHSP 2016 and the contractor method by calculating the unit cost of work per method. The unit cost of work is obtained by first calculating the basic unit price in the form of a multiplication between the coefficient and the unit price. The results showed that the contractor method was more effective and efficient. The calculation results show that the BOW is Rp3.574.900.000, while the 2016 AHSP method is Rp870.723.000, and the contractor method is Rp775.817.000. The comparison results find that the percentage of the BOW method is 75.64% greater than the 2016 AHSP method, while the 2016 AHSP method is 10.90% greater than the contractor method, then the percentage comparison of the BOW method is 78.30% greater than the contractor method.